Analytical methodologies using carbon substrates developed by pyrolysis - Benavidez, Tomás Enrique (2016)
As a viable alternative with respect to carbon-based materials prepared by vapor deposition, the pyrolysis of non-volatile organic precursors has allowed the development of substrates with advantageous properties towards the development of sensors. Considering the importance and versatility of these materials, this review provides a summary of representative articles describing the procedures and most important considerations linked to the fabrication of these films, and their characterization in terms of structure, thickness, topography, contact angle, as well as optical and electrochemical properties. The review focuses on analytical applications such as electroanalysis, biosensors, dielectrophoresis, and solid phases for separations published in the last five years but additional contributions outside this period have been included to provide readers background information to link the chemical functionality of the films with the corresponding performance. A series of promising directions for the future of the field are also described.